A Comprehensive Palliative Care Program at a Tertiary Cancer Center in Jordan. (March 2015) - Shamieh, Omar; Hui, David
Context: The palliative care program in King Hussein Cancer Center (KHCC) is growing rapidly to serve the needs of patients with cancer and their families. Objective: To describe the KHCC palliative care program and its integration into the oncology care. Methods: Narrative review of our palliative care program. Results: Patients with cancer at KHCC have access to an interprofessional palliative care at different settings. In 2012, the inpatient team saw 400 consultations and 979 referrals and admissions. The outpatient clinic had a total of 1133 patient visits. The home care program provided a total of 1501 visits. Our program is a regional center for education and training and actively conducts research. Conclusion: Our palliative care program may be a model for successful delivery of comprehensive cancer care in the Middle East.